Atomic-scale imaging of electronic nematicity in ferropnictides - Qiang-Jun Cheng; Yong-Wei Wang; Ming-Qiang Ren; Ze-Xian Deng; Cong-Cong Lou; Xu-Cun Ma; Qi-Kun Xue; Can-Li Song (Communications Materials)
Abstract Electronic nematicity, a correlated state characterized by broken rotational symmetry, has been recognized as a ubiquitous feature intertwined with unconventional electron pairing in various iron-based superconductors. Here we employ spectroscopic-imaging scanning tunneling microscopy to visualize atomic-scale electronic nematicity directly on FeAs planes of a prototypical ferropnictide BaFe2As2. Spatially, the nematic order appears as 4a Fe-spaced stripes (a Fe ~ 2.8 Å is the in-plane Fe-Fe distance) within homogeneously and orthogonally oriented nano-domains. The energy-resolved conductance maps reveal a pronounced energy-dependence of the nematic order parameter that experiences a sign change at approximately 30 meV. Moreover, the electronic nematicity exhibits pronounced sensitivity to single impurities and is notably suppressed by cobalt substitution for Fe atoms, promoting optimal superconductivity when nematic fluctuations are strongest. Our results provide pivotal experimental insights for developing a microscopic model of nematic order, thus paving the way to study its complex relationship with unconventional superconductivity.